Discrimination on transposition in rats - Ardila, Rubén (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The effects of three variables on transposition were investigated: time between training and test, type of discrimination, and distance along the relevant dimension between the training and the test stimulus pairs. Two levels each of time, discrimination and distance were used in a 2x2x2 factorial design. Subjects were 80 hooded rats. The apparatus was an adaptation of Munn’s visual discrimination apparatus. The majority of subjects in most groups transposed the discrimination; more transposition was observed with near than with far pairs of test stimuli, and more with delayed than with immediate presentation of the test pairs of stimuli. It was found that there was reliably more transposition of the discrimination to a pair of test stimuli which were near to the original discrimination pair than to a pair which were farther away along the relevant dimension. Type and time effects did not reach a conventional level of statistical significance, although they approached it. The graphic examination of the results indicates that no significant interactions were found. The findings were interpreted according to Spence’s theory of transposition. An alternative explanation in terms of adaptation level theory was also offered.